Coral bleaching and mortality in panama and ecuador during the 1997-1998 El Niño-Southern Oscillation Event: spatial/temporal patterns and comparisons with the 1982-1983 event - Glynn, Peter W.; Maté, Juan L.; Baker, Andrew C.; Calderón, Magnolia O. (Bulletin of marine science, 2001)
Bleaching and mortality of zooxanthellate corals during the 1997-98 El Niño-Southern Oscillation (ENSO) event are documented for eastern equatorial Pacific localities in Panama (Gulf of Chiriquí and Gulf of Panama) and Ecuador (Galápagos Islands and mainland coast). Overall, the very strong 1997-98 and 1982-83 ENSOs were similar in magnitude and duration, but varied spatially, resulting in different patterns of elevated sea temperature stress and coral responses during the two disturbance events. Two bleaching episodes occurred in the Gulf of Chiriquí, each coincident with high (≥30°C) in situ temperatures and warm water filaments visible in NOAA/NCEP SST fields. Coral mortality was significantly different among localities: Galápagos Islands (26.2%) > Gulf of Chiriquí (13.1%) > coastal Ecuador (7.0%) > Gulf of Panama (0%). Coral mortality was notably higher (52-97%) in the eastern equatorial Pacific in 1982-83 than in 1997-98. Coral mortality among most sites within localities was also significantly different. Highest coral mortalities occurred at offshore compared with nearshore sites in Panama, and at the Galápagos Islands compared with mainland Ecuador. Although species responses varied among localities, tissue death was especially high in Millepora spp., Pavona spp., Pocillopora spp., and Porites spp. Corals present in relatively deep (12-18 m), inter-reef habitats suffered lower rates of bleaching and mortality than similar and different species present in shallow (1-10 m) habitats. Bleached coral tissues in the Gulf of Chiriquí demonstrated a significant increase in zooxanthella density, but only a slight increase in chlorophyll a concentration over a 5 mo respite, from the end of the first bleaching event (October 1997) to the beginning of the second event (March 1998). The use of molecular DNA techniques to compare algal symbionts in bleached and healthy coral colonies revealed a strong correlation between bleaching severity and symbiont genotype, regardless of depth. In particular, one symbiont genotype (commonly found in the scleractinian genus Pocillopora in the Gulf of Chiriquí) was particularly resistant to bleaching, indicating that symbiont diversity can play an important role in explaining spatial and host systematic patterns of bleaching. Extreme reductions in abundance of some species populations in Panama have resulted in local extirpations. It is possible that Millepora boschmai, a Gulf of Chiriquí endemic hydrocoral, is now extinct. Remnant patches of Gardineroseris planulata that survived the 1982-83 ENSO in the Galápagos Islands have also disappeared following the 1997-98 event, causing local extinctions. Marked declines in external bioerosion and corallivore abundances in Panama before and after the 1997-98 ENSO should have less of an effect on surviving corals than in 1982-83 when such effects continued to degrade reefs long after the initial disturbance. Surviving corals in the Galápagos Islands are still subject to heavy grazing pressure by abundant echinoid populations. The response of eastern Pacific coral reefs to the 1997-98 El Niño cannot be fully understood without an appreciation of spatial/temporal variability and the historical stresses to which these reefs have been subject over the past 25+ yrs.